A comparative analysis before and after pandemic on environmental accounting public hospital - Putri, Sofie Yunida; Widajantie, Tituk Diah; Wilasittha, Acynthia Ayu (Goodwood Publishing, 2024)
Purpose: This study conducted a comparative analysis of the application of environmental accounting in hospitals before, during, and after the pandemic. Research methodology: This qualitative study used a comparative analytical approach. The data used in the research are primary data from interviews with three informants directly involved and secondary data from relevant financial information at the Regional Public Hospital. Mohamad Soewandhie, Surabaya. Results: The COVID-19 pandemic has impacted hospital environmental accounting. Hospitals commonly charge environmental costs for managing solid, liquid, and gaseous waste. The pandemic has increased hospital waste processing expenditure for these three classes. The growth in hospital waste and vendor waste processing costs due to increased demand, since hospitals cannot yet process their waste, are the main causes of the cost increase. Once the outbreak ended, hospitals could control the costs. Limitations: Financial data from the hospital was simply an illustration because it had to be integrated with the Surabaya City Government's financial reports and was not published. Contribution: It can be seen that it is important for hospitals to be able to budget environmental costs more seriously as a preventive measure if similar problems like the pandemic or other forces significantly occur in the future. Novelty: Previous similar research only studied how environmental accounting is implemented in a hospital and did not compare its implementation before, during, and after the pandemic.